The IKEA x UTS Future Living Lab as a Learning Laboratory - Brejzek, Thea; Wallen, Lawrence Paul (Interiority, 2021)
This article introduces the IKEA x UTS Future Living Lab, a design research collaboration between IKEA Australia and the University of Technology Sydney (UTS), founded in 2018. Authored by the Lab's two directors, the article traces the pedagogical and methodological approach of the IKEA x UTS Future Living Lab. Situated within the Educational Design Research (EDR) discourse, this article demonstrates the development of a productive dialogue between two contrary operating principles: that of infinite creativity afforded to design students, and that of rigorous design development towards mass manufacturing and market distribution by a major global player in the design industry. This article outlines how co-creation principles as practised by IKEA and peer-critique as a long-established pedagogical design school tool accelerate students' understanding of the complex processes involved in contemporary design and provide “real world” experiences in the production of design concepts and outcomes.